Spectroscopic investigations of plasma nitrocarburizing processes using an active screen made of carbon in a model reactor. (16th July 2018) - Puth, A; Hamann, S; Kusýn, L; Burlacov, I; Dalke, A; Spies, H-J; Biermann, H; Röpcke, J
Abstract: The active screen plasma nitrocarburizing technology significantly reduces the risk of cementite precipitation in the compound layer of nitrocarburized materials and of soot production compared to conventional plasma nitrocarburizing. In a laboratory-scaled plasma nitriding monitoring reactor, PLANIMOR, using an active screen made of carbon, low-pressure pulsed dc N2 –H2 plasmas have been studied by infrared laser absorption spectroscopy (IRLAS) techniques. Applying IRLAS, using tunable diode lasers (TDL) and a quantum cascade laser (QCL) as radiation sources, the evolution of the concentrations of eight stable molecular reaction products, C2 H2, C2 H4, CH4, HCN, NH3, CO, C2 H6, and C2 N2, and of the CH3 radical, have been monitored. By using the line ratio method, the rotational temperatures of HCN and CO could be determined in a range of 300–400 K and 300–500 K, respectively. Analysing the profile of the CH3 Q(3-3) absorption line, the gas temperature of this radical, i.e. the temperature in the vicinity of the plasma zone, has been found to range between 400–800 K. The concentrations of the detected molecular reaction products were found to be in the range of 10 12 –10 16 molecules cm −3 with HCN and NH3 as the most abundant reaction products. Additionally, the respective conversion efficiencies to the product molecules ( R C  ≈ 5 × 10 12 –2 × 10 16 molecules J −1 ) have been determined for different mixing ratios of N2 :H2 in the feed gas and plasma power values. Taking into account the concentrations of all carbon-containing species, a maximum of the carbon combustion of the screen material of up to 96 mg h −1 has been found for a N2 –H2 ratio of 1:1 and the highest plasma power of the screen of P screen  = 106 W.